Life in Family Buildings as a unique environment in Turkey - SABUNCUOĞLU, OSMAN TALAT (PAGEPRESS PUBL, 2019)
Family building (FB) is a building where residents of different flats are close relatives. Being quite common in metropolitan areas, these unique psychosocial environments remain underexamined. We aimed to research into the interactions within the family and psychosocial features of FBs. One hundred and one children living in FBs and FB-experiences of their parents were assessed by semi-structured interviews using K-SADS-PL. Mothers scored their satisfaction from FB-lifestyle in the scale of 0-100. The sample consisted of 35 girls and 66 boys. Mean age was 108 +/- 37.4 months. ADHD and anxiety disorders were the common diagnoses. Eighty-two families lived with paternal relatives. Number of relativeneighbors in the building changed between 2-10. Forty-one mothers scored <50 for their satisfaction; 58% believed FBs affected their children's symptoms negatively. Examining the perceived advantages and disadvantages of FBs, 'extreme criticism' and 'social support' were the decisive items to predict mothers' satisfaction levels. Having both positive and negative effects, FB-lifestyle seem to complicate interpersonal relations within the family. This study has revealed some preliminary findings, but further studies are required in the field.
Keywords: Child psychiatry; public health; family building; mental health; satisfaction; AGE